Upaya Pelestarian Gong Sibunguik di Desa Kebun Durian Kecamatan Gunung Sahilan Kabupaten Kampar Kiri Provinsi Riau - Jefrizal Jefrizal; Tengku Ritawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Finding out about the attempts to conserve Gong Sibunguik in Kebun Durian Village, Gunung Sahilan District, Kampar Regency, Riau Province, is the aim of the author's research. The three components of preservation are (1) protection, (2) development, and (3) exploitation, according to Sedyawati (2008: 152). Descriptive analysis using a qualitative approach is the strategy employed in this study. In this study, observational data collecting, interviews, and documentation were employed as data gathering methods. The study's findings indicate that measures to prevent the loss or destruction of cultural objects are part of its protection efforts. This can take the shape of records that serve as inspiration and a source of reference while digesting the performing arts. Increasing the number of musical instruments and Gong Sibunguik musician groups is one way to quantify this development endeavor. Efforts to improve the quality of Gong Sibunguik art are made by producing new music while preserving the traditional aspects of the art form. The purpose of this invention is to support traditional arts. Efforts to use it, namely Gong Sibunguik, are still made today, which is the same as modern arts, since Gong Sibunguik is an art form that is required for this event; without it, the event cannot take place as it does not adhere to local cultural standards. Furthermore, in Kebun Durian Village, Gong Sibunguik is typically present for circumcision ceremonies, marriages, greeting niniak mamak, and ba inai-inai. Gong sibunguik is typically done before the party's preparation (pre-party) at wedding celebrations.